Literatura y sociedad. Algunos ejemplos de la presencia de Jaime I en la Región de Murcia, a través de diversos contextos escritos. Siglos XIX y XX. - VILLA, RAMÓN DOMÉNECH (Scripta)
Each site is characterized by its particular hero. It would be very difficult to find two different heroes in shared physical spaces, even if they are border regions. In this days and age, this fact could be comparable to existing rivalries in certain sport competitions; besides, we may even look on the existence of certain parallelisms between these latter ones and those warfare situations produced in earlier centuries. The Region of Murcia, Andalusia and the Valencian Country competed each other in a particular feud for a monarchic prominence with clear family relationships during the XIII century. Given the predominance of one or another monarch, and regardless of their leading role we might ask ourselves many questions: Did all references to King James I disappeared, in the context of society Murcia, once that centuries passed by with another king as protagonist ? Would it be possible to find references to him in social contexts related to Murcia? Did the literature of the time play any role in this regard? Would Murcia citizens have created a non formal-context of historical learning?